An improved system for evaluating the adaptability of natural gas flooding in enhancing oil recovery considering the miscible ability. (1st December 2021) - Tang, Yong; Chen, Yulin; He, Youwei; Yu, Guangming; Guo, Xifeng; Yang, Qing; Wang, Yong
Abstract: Adaptability evaluation of reservoirs needs to be performed before natural gas flooding. However, the current evaluation methods consider the reservoir pressure and minimum miscible pressure (MMP) as separate parameters to evaluate the miscibility, which ignores the correlation between reservoir pressure and MMP. Also, the effect of reservoir pressure on injectivity is also neglected, while higher pressure than MMP may not improve the miscibility but increase the difficulty of gas injection. Furthermore, evaluation range of each index is inconsistent. Therefore, this paper proposes an improved evaluation system by introducing the miscible ability and optimizing the evaluation criteria to better evaluate the adaptability of natural gas flooding in enhancing oil recovery. The miscible ability is newly defined to evaluate the impact of reservoir pressure on miscibility, and multi-level evaluation model is further developed which includes 12 indexes based on reservoir/fluid/rock properties. The evaluation criteria are established by optimizing parameter intervals. The adaptability of BQ Oil field is assessed using Analytic Hierarchy Process (AHP) and fuzzy evaluation. Field application validates the reliability of the proposed evaluation system. It can be used to quickly evaluate the adaptability of natural gas flooding, which could improve success rate of natural gas flooding and reduce the costs. Highlights: An improved system for adaptability evaluation of natural gas flooding is proposed. Miscible ability is defined to evaluate the impact of pressure on miscibility. Multi-level evaluation model composed of 12 indexes is developed. Improved evaluation system can identify reservoirs suitable for natural gas flooding.